2020
DOI: 10.1111/bju.14985
|View full text |Cite
|
Sign up to set email alerts
|

Automated differentiation of benign renal oncocytoma and chromophobe renal cell carcinoma on computed tomography using deep learning

Abstract: Objectives To develop and evaluate the feasibility of an objective method using artificial intelligence (AI) and image processing in a semi‐automated fashion for tumour‐to‐cortex peak early‐phase enhancement ratio (PEER) in order to differentiate CD117(+) oncocytoma from the chromophobe subtype of renal cell carcinoma (ChRCC) using convolutional neural networks (CNNs) on computed tomography imaging. Methods The CNN was trained and validated to identify the kidney + tumour areas in images from 192 patients. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 32 publications
1
38
0
2
Order By: Relevance
“…Other models have incorporated MRI radiomics data with Gleason scores to train a ML model to predict clinically significant prostate cancer on MRI images with some success [50]. In renal cancer, ML models have been developed to accurately differentiate benign oncocytomas from RCC [51, 52]. Similarly, AI has been used to help in the planning of surgery by constructing three‐dimensional models of renal anatomy from CT scans.…”
Section: The Future Role Of Technology In Mdt Workingmentioning
confidence: 99%
“…Other models have incorporated MRI radiomics data with Gleason scores to train a ML model to predict clinically significant prostate cancer on MRI images with some success [50]. In renal cancer, ML models have been developed to accurately differentiate benign oncocytomas from RCC [51, 52]. Similarly, AI has been used to help in the planning of surgery by constructing three‐dimensional models of renal anatomy from CT scans.…”
Section: The Future Role Of Technology In Mdt Workingmentioning
confidence: 99%
“…They found that all five classifiers performed well at differentiating between the two with AUC values over 0.85 and concluded that their approach provides valuable preoperative diagnostic accuracy [29]. Other studies used DL approaches such as convolutional neural networks (CNN) to accurately classify chRCC and oncocytoma while also achieving 100% sensitivity in comparison with final pathology results [30]. Coy et al investigated the diagnostic value and feasibility of a DL-based renal lesion classifier to differentiate ccRCC from oncocytoma in 179 patients with pathologically confirmed renal masses on routine four-phasic CECT [28].…”
Section: Oncocytoma Vs Rcc Subtypesmentioning
confidence: 99%
“…Based on a CNN model and CT images, Baghdadi et al. ( 25 ) identified benign renal oncocytoma and ChRCC on images with an accuracy rate of 95%. Zhou et al.…”
Section: Discussionmentioning
confidence: 99%